Co-operatives in the new millennium - Selvaraju, R. (New Delhi : Vikas Pub. House : Distributors, UBS Publishers' Distributors, 1999)
In the Indian context; contributed articles.
Includes bibliographical references.
Rashid
Keywords: Cooperative societies -- India